2021
DOI: 10.1021/acsami.1c05437
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Multiwalled Carbon Nanotubes Enhance Bone Remodeling through Immunomodulatory Functions

Abstract: It has been reported that multiwalled carbon nanotubes (MWCNTs) can reportedly positively affect growth and differentiation of bone-related cells and therefore offer great potential in biomedical applications. To overcome negative immune responses that limit their application, specific doping and functionalization can improve their biocompatibility. Here, we demonstrated that nitrogen-doped carboxylate-functionalized MWCNTs (N-MWCNTs) enhance bone remodeling both in vitro and in vivo with excellent biocompatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
3
7
0
Order By: Relevance
“…[190] In addition, Li et al obtained nitrogen-containing multilayer carbon nanotubes by modification and found in in vitro studies that nitrogen-containing multilayer carbon nanotubes were able to activate both osteoclast and osteoblast activity, as confirmed by the biomarkers of both, tartrate-resistant acid phosphatase and alkaline phosphatase, and also identified that the osteoclast-associated signaling pathway RANKL was significantly downregulated and the osteoblast-related inducible osteogenic proteins BMP-2 and BMP-4 were activated. [191] In mice in vivo studies, nitrogen-containing multilayer carbon nanotubes also showed positive regulation of osteoblast-associated bone remodeling and osteoclast-associated bone resorption consistent with the in vitro study and the activation of macrophages that also contributed to bone remodeling. [191] These also show the important role played by MSCs in bone as well as cartilage repair.…”
Section: Nanomedicine Targeting Specific Stages Of Oasupporting
confidence: 73%
“…[190] In addition, Li et al obtained nitrogen-containing multilayer carbon nanotubes by modification and found in in vitro studies that nitrogen-containing multilayer carbon nanotubes were able to activate both osteoclast and osteoblast activity, as confirmed by the biomarkers of both, tartrate-resistant acid phosphatase and alkaline phosphatase, and also identified that the osteoclast-associated signaling pathway RANKL was significantly downregulated and the osteoblast-related inducible osteogenic proteins BMP-2 and BMP-4 were activated. [191] In mice in vivo studies, nitrogen-containing multilayer carbon nanotubes also showed positive regulation of osteoblast-associated bone remodeling and osteoclast-associated bone resorption consistent with the in vitro study and the activation of macrophages that also contributed to bone remodeling. [191] These also show the important role played by MSCs in bone as well as cartilage repair.…”
Section: Nanomedicine Targeting Specific Stages Of Oasupporting
confidence: 73%
“…In the present study, we demonstrated that DEXA can result in severe bone damage, which was consistent with our previous studies ( 11 , 25 ), indicating a success of the GIOP rat model. Simultaneously, our data showed that DEXA weakened serum AKP activity, which is recognized as an important marker of bone formation ( 26 ). We also verified that DEXA could increase CTSK expression, which is most abundant in osteoclasts ( 27 ), and decrease the expression of Runx2, an important osteoblast transcription factor, which was a benefit for bone formation ( 28 ), in GIOP rats.…”
Section: Discussionmentioning
confidence: 60%
“…Scientists have shown in mouse models that nitrogen-doped MWCNTs are better tolerated than the pristine MWCNTs, and induce a weaker in ammatory response [11]. Our investigation has demonstrated the enhancement of nitrogen-doped carboxylate-functionalized MWCNTs (N-MWCNTs) on bone growth with good biocompatability [12]. Therefore, N-MWCNTs offer immense opportunities as drug or biomolecule carriers and have great application potential in the treatment of diseases.…”
Section: Introductionmentioning
confidence: 80%
“…CNTs exhibit amazing functions in immunomodulation, cancer therapy, brain disorder treatment, tissue engineering, and drug delivery [9,10,12,23,24]. With the development of nanotechnology, the evaluation in drug delivery is more than ever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation